2021
DOI: 10.1186/s10020-021-00290-7
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tfh cell and subsets distribution are associated with low‐responsiveness to hepatitis B vaccination

Abstract: Background An estimated 5–10 % of healthy vaccinees lack adequate antibody response following receipt of a standard three-dose hepatitis B vaccination regimen. The cellular mechanisms responsible for poor immunological responses to hepatitis B vaccine have not been fully elucidated to date. Methods There were 61 low responders and 56 hyper responders involved in our study. Peripheral blood samples were mainly collected at D7, D14 and D28 after reva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Cellular immunological changes influenced by the cytokine environment are key in modulating effective vaccine-specific humoral responses. We assessed frequencies of circulating T follicular helper (cTfh) populations (39), critically involved in providing B cell help in infection and vaccination (4042), from the PBMCs of non-infected and S. mansoni -infected individuals by flow cytometry (S3 Fig). Frequencies of cTfh1 (low vs. high P=0.020) and cTfh2 cells (no vs. high P=0.012, low vs. high P=0.014) pre-vaccination (Fig 4A and 4B, S4 Table), were significantly lower in individuals with high CAA; and cTfh1 cells remained significantly lower at M7 (low vs. high P=0.031) and M12 (no vs. high P=0.030, low vs. high P=0.004) post-vaccination (Fig 4A, S4 Table).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular immunological changes influenced by the cytokine environment are key in modulating effective vaccine-specific humoral responses. We assessed frequencies of circulating T follicular helper (cTfh) populations (39), critically involved in providing B cell help in infection and vaccination (4042), from the PBMCs of non-infected and S. mansoni -infected individuals by flow cytometry (S3 Fig). Frequencies of cTfh1 (low vs. high P=0.020) and cTfh2 cells (no vs. high P=0.012, low vs. high P=0.014) pre-vaccination (Fig 4A and 4B, S4 Table), were significantly lower in individuals with high CAA; and cTfh1 cells remained significantly lower at M7 (low vs. high P=0.031) and M12 (no vs. high P=0.030, low vs. high P=0.004) post-vaccination (Fig 4A, S4 Table).…”
Section: Resultsmentioning
confidence: 99%
“…al. recently reported that lower responders to HepB vaccination had lower frequencies of cTfh cells and antibody-secreting plasmablasts (42); and Musaigwa and colleagues describe that S. mansoni infection specifically induces cell death in bone marrow plasmablasts and plasma cells (60). We show in addition to a lower frequency of cTfh cells in individuals with high CAA, a significant increase in activated B cells but a reduction in proliferating (antigen-specific) ASCs, ASCs expressing IgG and IgA, and that IgA + ASCs positively correlate with HepB titers.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating follicular helper T cells (cTfh) and subsets were shown to be involved in the immune response to hepatitis B vaccine injection in vitro , and the CXCR3-Tfh cell subset was preferentially activated when HBsAg stimulated PBMCs. One of the reasons for reduced antibody responses in the immune response to hepatitis B vaccination could be a decrease in cTfh cells and subset skewing ( 89 , 90 ). Approximately 5%–10% of healthy recipients of the hepatitis B vaccine did not produce HbsAb; nonresponse was associated with other factors such as age, gender, body mass, and route of injection, in addition to impaired Th cell response ( 91 ).…”
Section: T Cells and Measures Of Hbv-mtct Preventionmentioning
confidence: 99%
“…Nevertheless, a study of the low response to hepatitis B vaccination showed that although the number of total circulating Tfh cells was significantly lower in low responders, it was not due to an insufficient Tfh1 subpopulation. In contrast, cTfh2 and cTfh17 cells were severely shifted toward a cTfh1 phenotype in low responders [ 61 ]. Moreover, they demonstrated that miR-19b-1 and miR-92a-1 were associated with cTfh cell subset distribution and antibody production [ 61 ].…”
Section: Factors Affecting Vaccine Effectiveness By Regulating Tfh Ce...mentioning
confidence: 99%
“…In contrast, cTfh2 and cTfh17 cells were severely shifted toward a cTfh1 phenotype in low responders [ 61 ]. Moreover, they demonstrated that miR-19b-1 and miR-92a-1 were associated with cTfh cell subset distribution and antibody production [ 61 ]. Above all, the shifts in Tfh cell subsets were closely associated with protective antibody response production.…”
Section: Factors Affecting Vaccine Effectiveness By Regulating Tfh Ce...mentioning
confidence: 99%